2018
DOI: 10.1051/0004-6361/201731557
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric emission of the [OIII]λ5007 profile in narrow-line Seyfert 1 galaxies

Abstract: Context. Many active galactic nuclei (AGN) and particularly narrow-line Seyfert 1 (NLS1) galaxies, usually exhibit blueshifts and blue wings in several emission lines, which are mainly associated with outflows and strong winds. Although there is no clear evidence of the physical origin of the [OIII] blue wings, it has been suggested that they could be emitted from the inner parts of the narrow-line region (NLR). Aims. In order to study the radial velocity difference between the narrow component of Hβ and the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 64 publications
15
35
0
Order By: Relevance
“…a wing component with FWHM of ∼500 km s −1 −1500 km s −1 ). The blue-shifted [O III] broad-line component is thought to originate from outflows and strong winds near the AGN (Heckman et al 1981;Whittle et al 1988;Véron-Cetty et al 2001;Bian et al 2005;Komossa et al 2008;Crenshaw et al 2010;Cracco et al 2016;Schmidt et al 2018). We performed spectral decomposition again with this broad-line component (green color), present the results in the third panels in Fig.…”
Section: Spectral Decomposition Of Known Dagns and Dagn Candidatesmentioning
confidence: 99%
“…a wing component with FWHM of ∼500 km s −1 −1500 km s −1 ). The blue-shifted [O III] broad-line component is thought to originate from outflows and strong winds near the AGN (Heckman et al 1981;Whittle et al 1988;Véron-Cetty et al 2001;Bian et al 2005;Komossa et al 2008;Crenshaw et al 2010;Cracco et al 2016;Schmidt et al 2018). We performed spectral decomposition again with this broad-line component (green color), present the results in the third panels in Fig.…”
Section: Spectral Decomposition Of Known Dagns and Dagn Candidatesmentioning
confidence: 99%
“…It is suggested that the blue-shifted [O III]5007Å line is mainly related to nuclear outflows and strong winds [21,22,20]. The shocks produced from AGN can act as a source of excitation which leads to nuclear photoionization.…”
Section: Pos(heasa2019)031mentioning
confidence: 99%
“…Chen et al ( 2018) 1 (hereafter C18) classified 167 southern hemisphere galaxies as NLSy1s from the Six-degree Field Galaxy Survey (6dFGS) final data release (DR3) (Jones et al 2004(Jones et al , 2009 2 ; they derived flux-calibrated spectra and found strong correlations between the monochromatic luminosity at 5100 Å and the luminosities of H β and [O iii]λ5007 lines, with typical SMBH masses (10 6 -10 8 M ) and high Eddington ratios (a median of 0.96) for the AGN class. The survey of Schmidt et al (2018) 3 (hereafter S18) (28 galaxies) was focused on [O iii]λ5007 line profile asymmetries associated with outflows, confirming the correlation between the blueshift and FWHM of the line core, between the outflow velocity and the black hole mass and with the width of the broad component of H β. Removing objects common to the two catalogs gave a target list of 189 galaxies with declination < 10 • .…”
Section: Sample Selectionmentioning
confidence: 81%
“…We have presented a near-infrared spectroscopic survey (using the SOFI instrument on the ESO-NTT telescope) of narrow-line Seyfert 1 galaxies in the southern hemisphere. These have been sampled from the optical surveys of Chen et al ( 2018) and Schmidt et al (2018). We have examined the kinematics of the broad-line region, probed by the emission line width of hydrogen (Pa α and H β).…”
Section: Discussionmentioning
confidence: 99%